Effect of dried distillers grains with solubles withdrawal regimens on finishing pig performance and carcass characteristics - Jacela, J.Y.; Benz, J.M.; Prusa, K.J.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 962 pigs (PIC L337 × 1050, initial BW = 86.1 lb) were used to determine the effect of dried distillers grains with solubles (DDGS) withdrawal regimens on growth performance and carcass traits. Pigs were randomly assigned to 1 of 6 treatments (6 pens per treatment) balanced by average BW within gender. Treatments were: (1) a corn-soybean meal-based diet without DDGS fed for 89 d (control), (2) 30% DDGS fed from d 0 to 48 and 0% DDGS fed from d 48 to 89, (3) 30% DDGS fed from d 0 to 69 and 0% DDGS fed from d 69 to 89, (4) 30% DDGS fed from d 0 to 48 and 15% DDGS fed from d 48 to 89, (5) 30% DDGS fed from d 0 to 69 and 15% DDGS fed from d 69 to 89, and (6) 30% DDGS diet fed from d 0 to 89. All diets contained 3% added fat. Pig BW, ADG, ADFI, and F/G were determined every 14 d. At the end of the trial, carcass fat quality was evaluated. There were no treatment × gender interactions (P > 0.21) for any criteria evaluated. Although there were some differences in F/G within phases, there were no overall differences (P > 0.35) in growth performance among treatments. Final weight numerically decreased as total DDGS level increased. Feeding continuously or withdrawing DDGS from the diet, regardless of the amount or duration, had no significant effect (P > 0.39) on any of the carcass criteria measured. Pigs fed DDGS had increased (P < 0.01) iodine value of fat depots compared with control pigs. When the DDGS withdrawal duration increased (Treatments 6, 3, 2, and 1), iodine values for all fat depots decreased (linear; P < 0.01). Feed cost per pig was highest (P < 0.05) when 0% DDGS was fed or withdrawn 6 wk before marketing (Treatments 1 and 2) and lowest when DDGS was added in the diets until at least 3 wk before marketing (Treatments 3, 4, 5, and 6). However, the reduction in feed cost did not significantly improve (P > 0.57) revenue or income over feed cost. In summary, DDGS reduction or withdrawal 3 or 6 wk before market did not affect growth performance or totally alleviate its negative effect on carcass fat iodine value.
Keywords: Carcass; Dried distillers grains with solubles; Growth; Swine